The Diurnal Cycle of Urban Thermal Environment in Scale-model Street Canyons by Outdoor Field Measurement. (2017) - Wang, Q.; Li, Y.; Hang, J.; Peng, L.
Abstract: Building thermal mass is significant to influence urban climate. We performed scale-model field measurement of thermal environment and turbulence in summer of 2015 in Guangzhou, China. Two types of scale-model were used to arrange north-south street canyons (the 'empty' model with wall thickness of 1.5 cm and the 'sand model' in which all buildings are filled with sand producing bigger heat capacity) to conduct measurement over three days. The urban roughness layer turbulence and temperature characteristics in such idealized street canyons were investigated by using several instruments such as ultrasonic anemometer, temperature and humidity sensors, four component radiometers, infrared camera. We study velocity distribution, air temperature and basic characteristics of radiation in the idealized city. Especially focus on the different building heat storage impact on the thermal environment. The thermal mass in the empty model is much smaller than the sand model. Therefore, the measurements show that, during daytime wall temperature ( T wall ) and air temperature ( T air ) of empty model reached its peak earlier and this peak value is much higher than those of the sand model. After sunset, result is quite contrary. T wall in the sand model are higher than those in the empty model because the thermal storage of the former is much greater than the latter, but T air in these two models are similar because the measured location of T air is at the centre of street canyon and far from building walls . The street canyons were subjected to differential wall heating and overlying wind. As overlying wind is relatively weak, the heating of building walls may induce thermally driven circulation. A buoyancy parameter, , was used to demarcate thermal and inertial circulation regimes. When the street canyon was dominant by the wind, and the canyon velocities scaled by u 0 are approximately constant. When the thermal circulation becomes important, velocity in canyon and buoyancy parameter shows a relationship: .